Web Mapping Monitoring the Health of Trees and Urban Green Spaces in Baghdad (International Journal of Environmental Sciences, 2025)
Thriving urban forests are a testament to the vitality of metropolitan landscapes, whose role in purifying air, mitigating heat islands, and enhancing aesthetic appeal is unparalleled. web-based mapping applications have emerged as a promising solution, leveraging Geographic Information System (GIS) technology to integrate spatial data on tree locations with comprehensive information on species, age, and condition. This is particularly crucial in the case of Baghdad, the capital of Iraq, which has grappled with challenges such as rapid urbanization, war, and environmental degradation, all of which have exacerbated the plight of its arboreal assets. By harnessing the capabilities of web mapping applications, stakeholders in Baghdad can proactively monitor and manage the health of their urban trees and green spaces, enabling timely intervention to address issues like disease, pest infestations, and insufficient maintenance. This research endeavors to explore the application of web mapping technology in this context, examining existing platforms, assessing their efficacy, and proposing enhancements to improve their functionality and usability. The findings of this study will contribute to the development of more efficient and sustainable strategies for preserving the vitality of Baghdad's urban forests, ultimately enhancing the quality of life for its residents.